Sustainable Intensification of Winter Wheat for Improved Yield - Aastha Gautam; Luiz O. Pradella; Nicolas Giordano; Jorge Romero Soler; Jazmin Gastaldi; Romulo P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2025)
Preliminary evidence suggests that the current wheat grain yield of Kansas farmers is well below the yield potential of current varieties under the typical weather conditions experienced in the region. Consequently, this large yield gap is due to the conservative management of producers. To address whether current yields can be improved via intensive management, and whether such improvement is dependent on variety, we conducted a field study in a complete factorial treatment structure established in a split-plot design across six environments during the 2023–2024 growing season evaluating 10 winter wheat varieties (sub-plot) under two management practices (whole plots), namely intensive and standard. Intensive management included increased seed rate, seed treatment, fungicide application, and enhanced fertilization as compared to standard. Environmental conditions significantly influenced average grain yield, which ranged from 6.6 bushels per acre in Hays to 80.3 bushels per acre in Leoti. There were significant variety by environment and management by environment interactions, suggesting that variety performance and management effectiveness were location-dependent. Here, KS Bill Snyder performed best in Leoti (89.4 bushels per acre) and Phillipsburg (87.7 bushels per acre), while KS Providence excelled in McPherson (66.2 bu/a) and Manhattan (68.1 bu/a). Intensive management boosted average yield in Manhattan (30%), Phillipsburg (12%), and McPherson (11.2%) though the latter was only numerical. These findings emphasize that wheat yield improvement requires site-specific variety selection and management practices, reinforcing the importance of adaptive agronomic strategies to minimize the wheat yield gap in Kansas.
Keywords: winter wheat; sustainable intensification